Crescimento e produção de Pinus taeda L. na região dos Campos de Cima da Serra, Rio Grande do Sul. - Elesbão, Luiz Ernesto Grillo (2008)
This thesis was carried through as objective to study the growth and the yield of a stand of Pinus taeda L., implanted in 1987, in an initial spacing of 3 x 2 meters, located in the Farming Farm of the Ipê Ltda, in the city of Canela RS. This stand was management in high shaft system, with thinning underneath, for the wooden yield of great dimensions. To reach to the considered objectives two experimental hypotheses in submitted population to one had been formulated and two thinnings, beyond a control sample, without thinning. The thinnings had been carried through underneath with reduction of the basal area for levels of 28 m2ha-1. The growth in diameter, height and volume of the trees was adjusted with excellent precision for the Richards model of growth, presented a determination coefficient always superior of 0.97 and a low error standard of the estimate. To the 17 years, the total yield of the control sample, without thinning, was of 886.3 m3ha-1; with the accomplishment of one it roughs-hew of 756.6 m3ha-1, having resulting losses of yield in relation the 14,6% witness; with two thinnings, the yield was of 732.9 m3ha-1, having provoking losses of yield in relation the control sample, without thinning, of 17.3%. The executed thinnings had allowed a significant profit in diameter, until the 17 years of age, with the execution of one thinning an average diameter of 33.4 cm; with two thinnings an average diameter of 33.5 cm; e, an average diameter of 24.3 cm in the control sample, without thinning.